Sea-level change and facies development across potential Triassic–Jurassic boundary horizons, SW Britain (Geological Society Publishing House, 2004)
The Late Triassic to Early Jurassic aged succession of SW Britain (the Penarth and lower Lias Groups) comprises mudstone, sandstone and limestone strata deposited in a variety of marine to non-marine environments. Faunal and floral characteristics of these successions have led to the proposal that one location in SW England, St Audrie's Bay, should serve as the Global Stratotype Section and Point (GSSP) for the base of the Hettangian Stage and, thus, for the Triassic–Jurassic (Tr–J) boundary. The sections of SW Britain have also been used previously to infer sea-level change history and relate this to potential kill mechanisms associated with the Tr–J boundary mass extinction. Chemostratigraphic, biofacies and lithofacies data are used here to suggest alternative models of sea-level change in relation to possible Tr–J boundary horizons in the sections of SW Britain. A sea-level lowstand surface of erosion is inferred to occur within the Cotham Member of the Lilstock Formation, a unit deposited in an environment that was often subaerially exposed. In contrast to previous interpretations, the top surface of the overlying Langport Member (here inferred to be deposited on a carbonate ramp of depositional or tectonic origin) represents a drowning event of at least regional extent. All horizons regarded as plausible levels at which to place the Tr–J boundary based on fossil distributions lie within strata deposited during relative sea-level rise. However, it is doubtful whether the higher horizons proposed to mark the boundary faithfully record times of true biotic change on a global scale and, additionally, there is no positive evidence that sea-level fall had any relation to the genesis of proposed Tr–J marker horizons. It is unlikely that sea-level fall played a significant role in the Tr–J boundary extinctions in either a local or a global context.